Influence of Chest and Diaphragm Manual Therapy on the Spirometry Parameters in Patients with Cerebral Palsy: A Pilot Study. (13th February 2021) - Rutka, Magdalena; Myśliwiec, Andrzej; Wolny, Tomasz; Gogola, Anna; Linek, Paweł
Abstract : Objective . To evaluate the influence of manual therapy of the chest and diaphragm on the spirometry parameters in patients with cerebral palsy (CP). Method . The study was carried out on 20 youths with CP. All participated in 6 sessions (3 sham and 3 actual), with measurements of spirometry at baseline, postsham therapies 1 and 3, before actual therapy, and postactual therapy sessions 1 and 3. Two manual techniques were included: soft tissue mobilization of the chest and the diaphragm. Results . After the first actual therapy, there was a significant (p < 0.01 ) improvement in forced vital capacity (FVC) by 0.23 L (8% of the average predicted value) and forced expiratory volume in one second (FEV1 ) by 0.18 L (7% of the average predicted value) as compared to results before the therapy. Change in FVC parameter was clinically significant, whereas change in FEV1 was not clinically significant. After sham therapy, there was no improvement in spirometry parameters as compared to baseline results. Conclusion . Single-time manual therapy of the chest and diaphragm has a positive effect on FVC and FEV1 .